Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1159/000346234
|View full text |Cite
|
Sign up to set email alerts
|

The NeuroAiD II (MLC901) in Vascular Cognitive Impairment Study (NEURITES)

Abstract: Background: A substantial proportion of patients after nondisabling stroke are cognitively impaired compared to age- and education-matched community-dwelling controls. Moreover, poststroke patients who have ‘vascular cognitive impairment no dementia' (VCIND) of moderate severity have a high risk of incident dementia, dependency and death. Further studies are urgently needed to demonstrate effective cognition-enhancing therapies in VCIND given the scarcity of evidence-based treatment options. NeuroAiD is a trad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…All these clinical results are encouraging to pursue further exploration of NeuroAid as a new efficient therapeutic strategy against stroke. Two clinical trials with MLC901 are also ongoing for assessment in vascular cognitive impairment patients [23] and in New Zealand patients with traumatic brain injury (https://www.anzctr.org.au/Trial/ Registration/TrialReview.aspx?id=364449).…”
Section: Introductionmentioning
confidence: 99%
“…All these clinical results are encouraging to pursue further exploration of NeuroAid as a new efficient therapeutic strategy against stroke. Two clinical trials with MLC901 are also ongoing for assessment in vascular cognitive impairment patients [23] and in New Zealand patients with traumatic brain injury (https://www.anzctr.org.au/Trial/ Registration/TrialReview.aspx?id=364449).…”
Section: Introductionmentioning
confidence: 99%
“…it is estimated that dementia affects around 5-8% of those aged 65 years and older, and 30% of people older than 80 (1,5,11). vaD is the second most common cause of cognitive impairment in the elderly after AD, constituting 15-20% of all dementia worldwide (12,13). The incidence of vaD increases with age, without any significant difference between men and women (1).…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
“…The incidence of vaD increases with age, without any significant difference between men and women (1). The Canadian Study of Health and Ageing prospective cohort study of 10,253 elderly persons reported that patients with vCi had a higher rate of institutionalization and death, while half of those who had vCiND developed dementia within 5 years (13,14,15). it is also important to emphasize that stroke prevalence is 6 times higher in those with cognitive impairment relative to normal (16).…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
“…In addition, there are several ongoing studies on the use of NeuroAiD in poststroke cognitive impairment and TBI [17-19]. …”
Section: Introductionmentioning
confidence: 99%